Influence of dielectric layer thickness and roughness on topographic effects in magnetic force microscopy - Krivcov, Alexander; Ehrler, Jasmin; Fuhrmann, Marc; Junkers, Tanja; Möbius, Hildegard (Beilstein journal of nanotechnology, 2019)
Magnetic force microscopy (MFM) has become a widely used tool for the characterization of magnetic properties. However, the magnetic signal can be overlapped by additional forces acting on the tip such as electrostatic forces. In this work the possibility to reduce capacitive coupling effects between tip and substrate is discussed in relation to the thickness of a dielectric layer introduced in the system. Single superparamagnetic iron oxide nanoparticles (SPIONs) are used as a model system, because their magnetic signal is contrariwise to the signal due to capacitive coupling so that it is possible to distinguish between magnetic and electric force contributions. Introducing a dielectric layer between substrate and nanoparticle the capacitive coupling can be tuned and minimized for thick layers. Using the theory of capacitive coupling and the magnetic point dipole–dipole model we could theoretically explain and experimentally prove the phase signal for single superparamagnetic nanoparticles as a function of the layer thickness of the dielectric layer. Tuning the capacitive coupling by variation of the dielectric layer thickness between nanoparticle and substrate allows the distinction between the electric and the magnetic contributions to the MFM signal. The theory also predicts decreasing topographic effects in MFM signals due to surface roughness of dielectric films with increasing film thickness.